L’inclusione degli alunni con BES nelle attività del Laboratorio di Chimica - D’Agostino, Cristina; Solazzo, Daniele; Palumbo, Antonio; Rigardo, Christian; Di Mieri, Maria (Chimica nella Scuola, 2023)
The project, dedicated to the school inclusion of students with special educational needs (SEN), has demonstrated that the active and the constant dialogue among the theoretical chemistry teacher, the laboratory teacher and the support teacher, has allowed the planning of laboratory activities that has made these students able to practise more than an experience without being depleted of the fundamental contents and procedures.